A Departmental Initiative for Clinical and Translational Research. Issue 5 (April 2016) - Colombo, Christopher J; Baer, Stephanie; Blake, Lindsay; Bollag, Wendy B; Colombo, Rhonda; Diamond, Matthew; George, Varghese; Huber, Lu; Merchen, Lee; Miles, Kathy; Yang, Frances; Nahman, N Stanley
To encourage departmental research activities, the Department of Medicine of the Medical College of Georgia (MCG) introduced an internally funded Translational Research Program (TRP) in 2014. Patterned after the Vanderbilt Institute for Clinical and Translational Research, the program offers research studios for project guidance, research mentoring and the availability of limited financial support through research vouchers. Additional academic services include abstract reviewing, conducting research conferences, organizing departmental research programs for students, and offering courses in biostatistics. During the first 15 months of its existence, the TRP working group addressed 132 distinct activities. Research mentoring, publications, and the conduct of research studios or voucher approvals encompassed 49% of working group activities. Other academic services constituted the remaining 51%. Twenty-four per cent of TRP committee activities involved research mentoring of 32 investigators (25% faculty and 75% trainees). Mentored projects generated 17 abstracts, 2 manuscripts and 87, 000 in funds. The TRP conducted 13 research studios; trainees presented 54%. The TRP reviewed 36 abstracts for local and state organizations. Monthly research conferences and statistical courses were conducted and well attended. Our experience thus far indicates that a departmental TRP may serve to facilitate the growth of patient-oriented research with minimal financial support. It requires active engagement of volunteer faculty and departmental leadership willing to balance research with the other demands of the academic mission.